Analysis Methods Verification of Boron in River Water Using the Uv-Vis Spectrophotometer with Curcumin Complex as Alternative Practical Educations - Amri Setyawati (Universitas Islam Indonesia, 2019)
Boron is one of the industrial wastes included in the hazardous and toxic materials category. The purpose of this study was to determine river water sample levels and determine the value of linearity, RSD, and% recovery. The method used is under APHA - AWWA 4500 B. Some boron complexing compounds include curcumin in acetic acid, carminic acid, and quinalizarin, but in this study, curcumin complex are used because their sources in Indonesia are abundant. Curcumin gives a red complex color as an indication of the presence of boron in the sample. This phenomenon makes the learning process through practicum very interesting. Students can see the color change directly from orange to red. Students taught to produce reliable data and understand the importance of the chemist and analyst profession for the community through the practice of verification and validation methods, and the determination of the value of boron. Based on this study, it concluded that the Boron content in river water samples is 0.4766 mg / L. These results obtained from the straight-line equation that is y = 0.3446x - 0.0119 with R2 of 0.9976. The results of the RSD analysis are 0.028%, which states that the value is in the Horwitz TABLE range. Therefore, it can be accepted. Besides, the% Recovery is 86%; this value meets the analysis standard and is acceptable because it is in the range of 85% -115%. Finally, the measured boron levels in river water samples are still below the quality standard limits of the Republic of Indonesia Government Regulation Number 82 of 2001 concerning water quality treatment and water pollution control with a value of boron levels less than 1 mg / L. The boron content in a sample of river water in the Semarang area is still safe. Keywords: Boron, Practical Educations, Analytical Chemistry, Linearity, RSD, % Recovery.